Prinsip Maslahah, Keadilan, dan Etika Perdagangan Internasional dalam Perspektif Islam: Analisis Kasus Penutupan SPBU Swasta dan Larangan Eksploitasi - Muhammad Naufal Faqiih; Fadhli Suko Wiryanto; Muhammad Faiz Andreaz Fawwaz (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the application of the Islamic principles of maslahah, justice, and international trade ethics in analyzing the recent issues surrounding the closure of private fuel stations (SPBU swasta) and the prohibition of exploitative practices in Indonesia’s energy distribution sector. Using a qualitative descriptive approach, the research explores policy documents, academic literature, and news reports to understand how disparities in fuel supply, import policies, and market coordination impact fairness and public welfare. The findings indicate that technical inconsistencies in fuel standards, restricted access to supply, and unequal market power between state-owned and private distributors generate structural imbalances that contradict Islamic ethical values. Furthermore, the study reveals that inadequate transparency and misaligned distribution mechanisms have contributed to inefficiencies that harm consumers and smaller market players. Through the lens of maslahah, the analysis highlights the importance of ensuring that energy policies produce collective benefits while minimizing harm. The study concludes that integrating Islamic ethical principles into energy governance is essential to achieve equitable access, maintain market stability, and prevent exploitation within the national fuel distribution system.